Immunostimulatory activity of exopolysaccharides from probiotic Lactobacillus casei WXD030 strain as a novel adjuvant in vitro and in vivo - Lei Xiu (Taylor & Francis Group, 2018)
Exopolysaccharides act as mediators of cross-talk between probiotics and the host. Here, we found that EPS derived from probiotic Lactobacillus casei WXD030 strain (L-EPS) could modulate immune responses in vitro and in vivo. L-EPS could significantly enhance the proliferation and phagocytic activity as well as induce the production of NO, TNF-α, IL-1β and IL-6 in RAW264.7 cells. Furthermore, L-EPS could induce the maturation of BMDCs. In addition, L-EPS could largely increase the titres of OVA-specific antibodies and markedly enhanced T cell proliferation. Notably, L-EPS also increased expression of IL-4 and INF-γ expression in CD4+T cells. Consistently, when used as an adjuvant in vivo with the foot-and-mouth disease vaccine, L-EPS largely enhanced the FMDV-specific antibody production. Collectively, these results suggested that L-EPS derived from probiotic L. casei strain had adjuvant activity, which may be a safe and efficacious adjuvant candidate suitable for a wide spectrum of prophylactic and therapeutic vaccines.